Monitoring Greenland ice sheet buoyancy-driven calving discharge using glacial earthquakes. Issue 79 (September 2019) - Sergeant, Amandine; Mangeney, Anne; Yastrebov, Vladislav A.; Walter, Fabian; Montagner, Jean-Paul; Castelnau, Olivier; Stutzmann, Eléonore; Bonnet, Pauline; Ralaiarisoa, Velotioana Jean-Luc; Bevan, Suzanne; Luckman, Adrian
ABSTRACT: Since the 2000s, Greenland ice sheet mass loss has been accelerating, followed by increasing numbers of glacial earthquakes (GEs) at near-grounded glaciers. GEs are caused by calving of km-scale icebergs which capsize against the terminus. Seismic record inversion allows a reconstruction of the history of GE sources which captures capsize dynamics through iceberg-to-terminus contact. When compared with a catalog of contact forces from an iceberg capsize model, seismic force history accurately computes calving volumes while the earthquake magnitude fails to uniquely characterize iceberg size, giving errors up to 1 km 3 . Calving determined from GEs recorded ateight glaciers in 1993–2013 accounts for up to 21% of the associated discharge and 6% of the Greenland mass loss. The proportion of discharge attributed to capsizing calving may be underestimated by at least 10% as numerous events could not be identified by standard seismic detections (Olsen and Nettles, 2018). While calving production tends to stabilize in East Greenland, Western glaciers have released more and larger icebergs since 2010 and have become major contributors to Greenland dynamic discharge. Production of GEs and calving behavior are controlled by glacier geometry with bigger icebergs being produced when the terminus advances in deepening water. We illustrate how GEs can help in partitioning and monitoring Greenland mass loss and characterizing capsize dynamics.